Level of autistic traits in neurotypical adults predicts kinematic idiosyncrasies in their biological movements - Lewis, Gregory F.; daSilva, Elizabeth B.; Aghajani, Mohammad; Date, Surabhi; Jaime, Mark (Frontiers in Integrative Neuroscience, 2024)
Introduction Over the last decade of research, a notable connection between autism spectrum disorder (ASD) and unique motor system characteristics has been identified, which may influence social communication through distinct movement patterns. In this study, we investigated the potential for features of the broader autism phenotype to account for kinematic idiosyncrasies in social movements expressed by neurotypical individuals. Methods Fifty-eight participants provided recordings of point-light displays expressing three basic emotions and completed the Autism Spectrum Quotient (AQ). We extracted kinematic metrics from the biological movements using computer vision and applied linear mixed-effects modeling to analyze the relationship between these kinematic metrics and AQ scores. Results Our results revealed that individual differences in the total AQ scores, and the sub-scale scores, significantly predicted variations in kinematic metrics representing order, volume, and magnitude. Discussion The results of this study suggest that autistic traits may intricately influence the movement expressions at the microlevel, highlighting the need for a more nuanced understanding of the potential endophenotypic characteristics associated with social movements in neurotypical individuals.